Face to Face or Online Learning: Students’ Perspectives on Blended Learning in Indonesia - Endang Setyaningsih (English Department - University of Sultan Ageng Tirtayasa, 2020)
The implementation of blended learning (BL) continues to grow and encouraged in many contexts of teaching. While previous investigations had largely focused on BL implementation and effect on learning, the number of studies highlighting the students’ point of view is limited. This survey study investigated students’ perspective on the implementation of BL in the context of tertiary education. The respondents of this study were 75 students from three tertiary institutions in Indonesia. The data were collected utilizing a questionnaire which was adapted from and developed based on the PLEQ II to meet this present context of the study. Thematic analysis of five possible situations of blended learning resulted in the identification of the attributes that hinder and facilitate learning in the context of BL from the perspective of the students. This study indicated that students preferred and felt that they learned better in face to face session. The students acknowledged advantages but found online sessions more problematic. The study also confirms the self-regulatory attribute as a vital component in blended learning. The findings imply that blended learning, as opposed to blended teaching, requires careful tailoring to meet specific context and purpose of learning.